Ремесла українського народу - Манько, К. Є. (ХНУРЕ, 2020)
This work is devoted to Ukrainian and national crafts. It tells about their history of development, how they have changed over the years.There is the story of the origin of crafts, how they were varying, depending on the political system, where they were most common.
Keywords: культурне розмаїття; українознавство; традиції; культура